Sharing Perspectives: Inviting Playful Curiosity Into Museum Spaces Through a Performative Score - Løppenthin, Andreas; Bjerre Jensen, Dorte; Vesper, Cordula; Roepstorff, Andreas; Dumit, Joseph (Frontiers in Psychology, 2022)
We report on the performative score ‘Sharing Perspectives’ from the art/science research collaboration, Experimenting, Experiencing, Reflecting. Sharing Perspectives (SP) is developed as a score, inspired by choreography and the postmodern dance form Contact Improvisation, to stage exploration and improvisation, exploring uncertainty, creativity, togetherness, and the relationship between bodies and between bodies and space and artworks. The SP score acts as an experiment in how a brief intervention may affect the way art exhibitions are experienced, exploring how deeper and more sensorial engagement with art may be facilitated, for the benefit of visitors, galleries and artists. Based on questionnaires and qualitative interviews with participants during the Olafur Eliasson exhibition ‘In Real Life’ at the Tate Modern in London in November 2019, we explored how the SP score modulates a playful mode of being, enhancing the experience of a museum art exhibition as a space of transformation and reflection. We find that the SP score encourages curiosity, which allows participants to recognize their habits for art and instead experience art slowly, recognize their comfort zones and move past them. As the score enacts a sensorial and playful approach to the exploration of the exhibition, participants experience a breaking of boundaries between each other, towards the other visitors, as well as to the artworks and the space itself, prompting an experience of being part of the exhibit as a whole. We discuss how the SP score invites a slowness and curiosity that takes on characteristics of play, which can change the participants’ appreciation of an art space.